2015
DOI: 10.11113/jt.v73.4324
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Green Retrofitting Implementation in Non Residential Existing Buildings

Abstract: Sustainability has been the latest value added service in the facility management field. However, the practice of sustainability in the facility management field is not well recognized and understood by the facility management team. As a result, building sector account to be the largest source of greenhouse gas emissions around the world. In fact, there is a strong business case for green building, yet green buildings represent the next phase of buildings. Since, the majority of the existing stock of buildings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…The aggregated CO 2 emissions are calculated based on the use of gas ( 5) and electricity (6). For this purpose, a fixed CO 2 emission rate ( ) is applied to the aggregated gas flows.…”
Section: Emissions Calculationmentioning
confidence: 99%
See 1 more Smart Citation
“…The aggregated CO 2 emissions are calculated based on the use of gas ( 5) and electricity (6). For this purpose, a fixed CO 2 emission rate ( ) is applied to the aggregated gas flows.…”
Section: Emissions Calculationmentioning
confidence: 99%
“…For example, several techno-economic models have been proposed for the assessment of low carbon interventions. At a disaggregated level, models for insulation upgrades [4][5][6], placement of heating options (e.g., considering various technologies and emitters [7][8][9]), and installation of electricity generation and electro-thermal alternatives (e.g., PV and CHP [10][11][12]) have been proposed. Considering the benefits of aggregation, models of district heating networks [13,14] and private-wire/microgrid arrangements [15][16][17][18] have also been advanced.…”
Section: Introductionmentioning
confidence: 99%
“…Li and Xia [15] used the equivalent thermal parameter model to simulate air conditioners for Demand Response Programs (DR). And Jagarajan et al [16] proposed a simplified thermal model in the stochastic state-space and performance maps for predicting the coupled thermal response of a cooling unit. While Husin et al [17] implemented an aggregated model of a house cooling unit to establish the relationship between the external environment, indoor temperature, and the power consumption of the cooling system.…”
Section: Research Backgroundmentioning
confidence: 99%
“…However, due to an absence of collateral in private buildings, a great deal of reluctance is seen amongst financial institutions for the provision of funds to such buildings. Jagarajan et al (2015) suggested that initial capital costs, changes in the pricing of green materials and lack of funding further contribute toward the financial barrier of retrofitting. Furthermore, Marker et al (2014) suggest that over 50 per cent of barriers to green retrofitting is owed to unattractive returns on investments.…”
Section: Barriers Of Green Retrofittingmentioning
confidence: 99%